(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article analyzes Bubuyna Oruzbaeva’s contribution to Kyrgyz terminology, her achievements, and linguistic means of manipulation. It examines the influence of terms in political discourse and their effect on public consciousness. Based on the research, recommendations and conclusions regarding the use of terminology are presented.